A comparison of online fraud prevention disclosure in Malaysian and Indonesian public universities / Corina Joseph …[et al.] - Joseph, Corina; Utami, Intiyas; Madi, Nero; Rahmat, Mariam; Tunga Janang, Jennifer; Omar, Normah (Universiti Teknologi MARA, 2021)
This study aimed to examine the extent of fraud prevention information disclosure on websites of Malaysian and Indonesian public universities using the Legitimacy Theory (LT). Based on a content analysis of fraud prevention information disclosed on the websites of 20 Malaysian and 86 Indonesian public universities using a newly developed University Fraud Prevention Disclosure Index, it was found that Malaysian public universities on average disclosed 13 items under study compared to just 11 items disclosed by the universities in Indonesia. Overall, the level of disclosure for both countries was low. Malaysian public universities are more vigilant and stronger in the Internal Audit and Bursary aspects, whilst its Indonesian counterparts are better in five aspects: integrity and governance, policy, fraud prevention strategies, fraud response procedure, and raising awareness. Public universities in both countries need to put more effort in disclosing fraud prevention information on their websites. Websites should be used to legitimize societal accountability in the quest to look more transparent in accounting procedures and procurement guidelines. This paper adds to the literature by integrating two elements of sustainable development goals (quality education (SDG No 4) in an effective, accountable, and transparent institution (SDG No 16) using the LT to enhance the understanding of fraud prevention disclosure on universities’ websites.